Worsening or ‘pseudo-worsening’ renal function? The prognostic value of hemoconcentration in patients admitted with acute heart failure - José Luís Martins; Luís Santos; Ana Faustino; Jesus Viana; José Santos (Revista Portuguesa de Cardiologia, 2018)
Introduction: Renal insufficiency, as evidenced by an increase in creatinine, is associated with higher mortality in patients with acute heart failure (AHF). Conversely, hemoconcentration (HC) in AHF is associated with lower mortality, but can also cause an increase in creatinine. Our aim was to assess the prognosis of HC in patients hospitalized for AHF presenting with or without worsening renal function (WRF). Methods: A total of 618 consecutive patients admitted for AHF were included. WRF was defined according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria and HC was defined as an elevation of hemoglobin during hospitalization compared to the admission value. Six-month all-cause mortality was analyzed. Results: The patients’ mean age was 79±11 years; 58% were women. Mortality at six months was 38% and 49% of patients had WRF. HC occurred in 38.9% of patients with WRF and was associated with improved survival (HR 1.6, 95% CI 1.10-2.34; p=0.02) compared to WRF without HC. HC was associated with better survival in KDIGO stages 1 and 2 (HR 1.8; 95% CI 1.1-2.8; p=0.01). For patients without chronic kidney disease (CKD) with WRF in stages 1 and 2, HC was associated with significantly better survival (HR 2.3; 95% CI 1.2-4.2; p=0.01). Conclusion: In patients admitted for AHF without renal failure or CKD, WRF with HC is associated with a better prognosis, similar to that of patients without WRF, and should therefore be reclassified as ‘pseudo-WRF’. Resumo: Introdução: Alterações na função renal com aumento da creatinina têm sido associadas a maior mortalidade em doentes com insuficiência cardíaca aguda (ICA). Já a hemoconcentração na ICA tem-se associado a redução da mortalidade, é também uma causa de elevação da creatinina. Avaliar o prognóstico da hemoconcentração (HC) em doentes hospitalizados por ICA com e sem agravamento da função renal (AFR). Métodos: Analisados 618 doentes consecutivos admitidos por ICA. Definido agravamento da função renal de acordo com os critérios KDIGO e HC como elevação da hemoglobina durante a hospitalização comparativamente à admissão. Avaliada morte por qualquer causa aos seis meses. Resultados: A idade média foi 79 ± 11 anos; 58% mulheres. A mortalidade aos seis meses foi de 38%; 49% dos doentes tiveram AFR. HC ocorreu em 38,9% dos doentes com AFR e associou-se a maior sobrevivência após ajuste de fatores demográficos e comorbilidades (HR 1,6; IC95%: 1,06–2,33; p=0,026), comparativamente a AFR sem HC. Na avaliação por estádios KDIGO, HC associou-se a maior sobrevivência nos estádios 1 e 2 (HR 1,8; IC95%: 1,1–2,8; p=0,01). Nos doentes com doença renal crónica (DRC) com AFR nos estádios 1 e 2, a HC esteve associada a maior sobrevivência (HR 2,3, IC95%: 1,2-4,2, p=0,01). Conclusão: Em doentes admitidos por ICA sem falência renal ou DRC, o AFR com HC está associada a bom prognóstico. O seu prognóstico é similar a doentes sem AFR e deverá assim ser reclassificado como «pseudo-AFR». Keywords: Cardiorenal syndrome, Worsening renal function, Hemoconcentration, Palavras-chave: Síndrome cardiorrenal, Agravamento da função renal, Hemoconcentração